The expression levels of MicroRNA-146a, RANKL and OPG after non-surgical periodontal treatment - Mandana Sattari; Ramezan Ali Taheri; Reza ArefNezhad; Hossein Motedayyen (BMC, 2021)
Abstract Objective MicroRNA-146a (miR-146a) is a regulator of inflammatory response. Periodontitis is a disease with immune pathophysiology of the periodontium in which the inflammation results in the destruction of the soft tissues and alveolar bone. Therefore, the aim of this study was to investigate the expressions of miR-146a, OPG, and RANKL in diseased and healthy periodontal tissues to understand whether miR-146a expression level may associate with OPG and RANKL mRNA levels and OPG/RANKL ratio after non-surgical periodontal treatment. Methods The levels of miR-146a, RANKL, and OPG in gingival tissues from patients with generalized periodontitis stages II and III and grades A and B (n = 15, group A), patients with generalized periodontitis stages III and IV and grade C (n = 15, group B), and healthy individuals (n = 10) were determined by real-time PCR. The associations of miR-146a expression with OPG and RANKL levels were evaluated. Results The levels of miR-146a in two subgroups within periodontitis patients were significantly higher than healthy subjects (P < 0.0001). MiR-146a showed the increased level in group A of patients compared with group B (P < 0.05). Clinical parameters such as probing depth (PD) and clinical attachment loss (CAL) were significantly higher in patients than control group (P < 0.05). The levels of OPG and RANKL were increased in patients compared with healthy subjects, although the elevated levels were not statistically significant. MiR-146a was not associated with OPG and RANKL levels and OPG/RANKL ratio. Conclusions The results of this study failed to show the associations of miR-146a level with OPG and RANKL levels and OPG/RANKL ratio in periodontitis after non-surgical periodontal treatment.